Goat Performance of Peanut Goat with Supplementation of Feed Wafers Containing Lamtoro Taramba Leaves at Sumbawa Global Farm - Munandar, Imam (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2024)
Wafer feed is a form of compacted feed to reduce storage space. The ingredients used consist of lamtoro leaves, bran, molasses which are formulated according to the nutritional needs of the feed. This study aims to determine the best level of feed wafers made from lamtoro leaves given to kacang goats. The experimental design used a completely randomized design (CRD) with 3 treatments 4 replicates P1 = 10% feed containing lamtoro leaves, P2 = 12% feed containing lamtoro leaves, P3 = 14% feed containing lamtoro leaves. The results showed that the production performance of kacang goats had a significant effect (P<0.05) on increasing ADG, feed consumption, feed efficiency for kacang goats. It was concluded that the level of giving lamtoro leaf wafers of 12% was the best level